The Effect of Two Weeks of L-Carnitine Supplementation on Muscle Damage Markers Following Intense Aerobic Activity in Female Karate Players - Torab Beigi , Zohreh; Ilbeigi, Saeed; Saghebjoo, Marziyeh; Jafari, Mozhgan (International Journal of Sport Studies for Health, 2025)
Background and Aim: This study investigated the effect of two weeks of L-carnitine supplementation on muscle damage markers, specifically creatine kinase (CK) and lactate dehydrogenase (LDH), following intense aerobic activity in female karate athletes. Methods: This experimental study employed a repeated-measures design with a control group. Twenty-one female karate athletes from Mashhad were selected based on inclusion criteria and randomly assigned to either the L-carnitine or placebo group. For 14 days, the L-carnitine group received 2 grams of L-carnitine daily in capsule form, while the placebo group received 2 grams of starch capsules. On day 15, participants underwent a fasting blood draw before performing an endurance running test. Subsequent blood samples were collected at 5 minutes, 2 hours, and 24 hours post-endurance test. Data analysis was performed using repeated-measures ANOVA with SPSS version 24, with a significance level set at p<0.05. Findings: The results indicated a significant increase in CK and LDH levels immediately after activity compared to immediately before activity within the L-carnitine group (p<0.05). No other significant differences were observed in subsequent pairwise comparisons within this group. Conversely, the placebo group showed significant increases in CK and LDH levels immediately, 2 hours, and 24 hours after activity compared to two weeks before the activity (p<0.05). Furthermore, a significant difference was observed between the L-carnitine and placebo groups for CK and LDH levels immediately, 2 hours, and 24 hours after activity, with significantly higher values in the placebo group. Conclusion: These findings suggest that two weeks of L-carnitine supplementation at a dose of 2 grams may potentially help prevent further muscle breakdown up to 24 hours following intense aerobic activity.